(untitled) (Vietnam Journal of Community Medicine, 2024)
Objectives: To assess the percentage of children’s parents having sufficient knowledge toward disease and diphtheria vaccination in Dak Nong province in 2021. Methods: The study was performed between May to June 2021 using a descriptive cross-sectional design among parents of children under 5 years old in Dak Nong province. Data was collected via a structured questionnaire. Results: A total of 238 parents completed the survey, there is a mean age of 29 (25-33) years. 78.6% of parents had sufficient knowledge of disease and diphtheria vaccination. There was a significant relationship between knowledge and preventive practice of diphtheria (p<0.001). Conclusion: The percentage of parents with correct knowledge about the disease and vaccination against diphtheria is relatively high, accounting for 78.6%, knowledge is related to vaccination practice. Therefore, the health education program for the people should be continued to improve knowledge and contribute to increasing the rate of the fully vaccinated practice.